PENGEMBANGAN LKPD BERBASIS GAME-BASED LEARNING (GBL) PADA MATERI RAGAM BUDAYA INDONESIA DI KELAS V SEKOLAH DASAR - Bobby Kelvin; Rury Rizhardi, Ida Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the results of developing a student worksheet (LKPD) based on game-based learning that is valid and practical for the topic of Indonesian cultural diversity in Grade V of elementary school. The research used the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects were fifth-grade students at SD Negeri 22 Indralaya. Data collection techniques included questionnaires, interviews, and documentation. Data analysis was carried out through validity and practicality analysis. The results of expert validation showed an average percentage of 94.18%, categorized as